2019
DOI: 10.3390/su11195362
|View full text |Cite
|
Sign up to set email alerts
|

Studies of a Rotary–Centrifugal Grain Grinder Using a Multifactorial Experimental Design Method

Abstract: A scientific and technical literature review on machines designed to grind fodder grain revealed that the existing designs of grinding machines—those based on destruction by impact, cutting, or chipping—have various drawbacks. Some disadvantages include high metal and energy intensity, an uneven particle size distribution of the ground (crushed) product, a high percentage of dust fraction, the rapid wear of work tools (units), and heating of the product. To eliminate most of the identified shortcomings, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A study of installations based on vane pumps [1,2,3,4,5,6,7,8], it was found that the rotational speed n from 1750 to 3000 min -1 is not always effective, although even with these values high performance indicators. Therefore, in experimental studies, we proceed from the fact that we take synchronous speeds of rotation of the electric motor (respectively, it will be the same for the impeller) n = 750, 1000 and 1500 min -1 , but for more accurate readings we take a step of 250 min -1 , respectively, points will be next n=750, 1000, 1250, 1500 and 1750 min -1 .…”
Section: Theoretical Methodological and Empirical Basementioning
confidence: 99%
“…A study of installations based on vane pumps [1,2,3,4,5,6,7,8], it was found that the rotational speed n from 1750 to 3000 min -1 is not always effective, although even with these values high performance indicators. Therefore, in experimental studies, we proceed from the fact that we take synchronous speeds of rotation of the electric motor (respectively, it will be the same for the impeller) n = 750, 1000 and 1500 min -1 , but for more accurate readings we take a step of 250 min -1 , respectively, points will be next n=750, 1000, 1250, 1500 and 1750 min -1 .…”
Section: Theoretical Methodological and Empirical Basementioning
confidence: 99%
“…In the centrifugal-impact shredder, the rotor's blade is used to accelerate a grain to a speed of 80...100 m/s to be destroyed by a blow against a stationary reflector on the deck. In this case, grain destruction is much more effective than when grinding with free hammer blows [5,6]. This produces a shredded material with a more uniform granulometric composition that meets zootechnical requirements while the specific energy consumption is 3.3...4.5 kWh/t [6][7][8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It is possible to obtain shredded material with an aligned granulometric composition that meets zoo-technical requirements when grinding grain at centrifugal-impact crushers [5,6]; this ensures the specific energy consumption within 3.3…4.5 kWh/t [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…While the results offer insights for low-noise grass crusher design, the crushing performance of the grass crusher has not been correspondingly investigated and analyzed. Marczuk, A. et al [11] presented a design for a rotary centrifugal grain mill aimed at addressing issues related to uneven particle size distribution and high dust content in milled products. They utilized a multifactor experimental method to construct a prediction model of factors and indicators, enabling the determination of optimal parameter combinations.…”
Section: Introductionmentioning
confidence: 99%